2014
DOI: 10.1016/j.jvolgeores.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Fluid circulation pattern inside La Soufrière volcano (Guadeloupe) inferred from combined electrical resistivity tomography, self-potential, soil temperature and diffuse degassing measurements

Abstract: International audienceAfter a drastic decline in 1983, hydrothermal activity at La Soufrière lava dome (Guadeloupe, Lesser Antilles) has been progressively increasing in the summit area since 1992, raising the threat of a renewed eruptive activity. To better constrain the geometry of the hydrothermal system, an extensive high-resolution self-potential survey was performed on the dome and three multi-method profiles combining electrical resistivity tomography, self-potential, ground thermometry and soil CO 2 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 62 publications
3
44
1
Order By: Relevance
“…; Mauri, Williams‐Jones and Saracco ; Brothelande et al . ) and detection of contaminant plumes (e.g. Martinez‐Pagan et al .…”
Section: Introductionmentioning
confidence: 99%
“…; Mauri, Williams‐Jones and Saracco ; Brothelande et al . ) and detection of contaminant plumes (e.g. Martinez‐Pagan et al .…”
Section: Introductionmentioning
confidence: 99%
“…Results in this paper imply that for the common practice of performing a DTM, one has to take particular care during a geophysical survey. For the example of volcano surveys (Finizola et al, 2002;Brothelande et al, 2014Brothelande et al, , 2015, or engineering applications (hydraulic structures [Fargier et al, 2014]), the desired ERI resolution is often weaker than the DTM variations between two adjacent electrodes. In this case, our experience shows that the use of a very accurate surface description must become of major importance when the variation between interelectrode spacing and surface electrode spacing (at the same scale) is greater than 30%.…”
Section: Discussionmentioning
confidence: 99%
“…hydrothermal system of specific lava domes at given points in time (Bedrosian et al 2007;Finn et al 2007;Finn and Deszcz-Pan 2011;Brothelande et al 2014). Such studies are logistically challenging and cannot provide information about temporal variations of a system unless they are repeated.…”
Section: Geophysical and Geochemical Investigations Have Been Used Tomentioning
confidence: 99%
“…At the Mount St. Helens lava dome (Bedrosian et al 2007), electrical resistivity surveys revealed that meteoric water circulated in the young dome due to heat input from a nearsurface magmatic source, but did not capture longer-term changes occurring in the hydrothermal system as the dome subsequently cooled. Aeromagnetic and electromagnetic surveys of Cascade volcanoes (Finn et al 2007;Finn and Deszcz-Pan 2011) and the La Soufriere volcano (Brothelande et al 2014) have indicated the presence of water and altered material in specific locations in the edifices at the times of the surveys, but provide limited information about flow pathways within the hydrothermal systems and how they might be expected to have evolved or evolve in the future..…”
Section: Geophysical and Geochemical Investigations Have Been Used Tomentioning
confidence: 99%